Social determinants of prescribed and non-prescribed medicine use - García-Altés Anna; Rodríguez-Sanz Maica; Pasarín M Isabel; Daban Ferran; Villalbí Joan R; Zara Corinne; Borrell Carme (BMC, 2010)
Abstract Background The aim of the present study was to describe the use of prescribed and non prescribed medicines in a non-institutionalised population older than 15 years of an urban area during the year 2000, in terms of age and gender, social class, employment status and type of Primary Health Care. Methods Cross-sectional study. Information came from the 2000 Barcelona Health Interview Survey. The indicators used were the prevalence of use of prescribed and non-prescribed medicines in the two weeks prior to the interview. Descriptive analyses, bivariate and multivariate logistic regression analyses were carried out. Results More women than men took medicines (75.8% vs. 60% respectively). The prevalence of use of prescribed medicines increased with age while the prevalence of non-prescribed use decreased. These age differences are smaller among those with poor perceived health. In terms of social class, a higher percentage of men with good health in the more advantaged classes took non-prescribed medicines compared with disadvantaged classes (38.7% vs 31.8%). In contrast, among the group with poor health, more people from the more advantaged classes took prescribed medicines, compared with disadvantaged classes (51.4% vs 33.3%). A higher proportion of people who were either retired, unemployed or students, with good health, used prescribed medicines. Conclusion This study shows that beside health needs, there are social determinants affecting medicine consumption in the city of Barcelona.